Seed characteristics, germination behavior and dormancy type of selected Bunium persicum B. Fedtsch. ecotypes - Ghasemi, Mohsen (2012)
Bunium persicum (Boiss.) B. Fedtsch. (Black cumin) is a perennial herbaceous plant from the Apiaceae family. This species is an economically important medicinal plant and grows wildly in cold temperate and the desert regions from southeastern Europe to southern Asia. Dried B. persicum fruits are used worldwide as culinary spice. This spice is not cultivated in Iran because of seed dormancy and is only found in certain natural habitats. Despite its importance, there is no comprehensive information on seed characteristics, germination behavior, and type of dormancy in B. persicum. The objectives of this study were to characterize the anatomical and morphological structures of seed, germination behavior and to determine the type of seed dormancy that exists. Seeds of five ecotypes were collected from different geographical locations in Iran. Histological studies were done to evaluate the anatomical and morphological differences in seeds among the ecotypes. Although there are variations among B. persicum ecotypes in their seed size and shape, all of them have similar underdeveloped linear embryo structure surrounded by endosperm and seed coat. The seed germination behavior, under different temperatures and GA3 concentrations was found to be different among ecotypes. It was found that the seeds of ecotypes collected from dry areas had the lowest percentage of germination. A narrow range of temperature (i.e. 10-15⁰C) was found to be effective for breaking the seed dormancy. The fluctuating temperature (5⁰C/15 ⁰C) during the imbibition stage provided the best condition to stimulate germination. Intact seeds imbibed water under normal laboratory conditions which indicates that the seed coat of B. persicum is permeable to water; thus, the seeds do not have physical dormancy. Exogenous application of GA3 was found to be effective in breaking seed dormancy to the extent that the increase in GA3 concentration led to the increase in germination percentage. In a seed with underdeveloped linear embryo, as found in this species, the embryo has to grow to the full length requiring cold temperature and GA3 to break the dormancy and promote embryo growth. Therefore, the seed of this species has intermediate complex morphophysiological dormancy (MPD).